“RESISTENSI TOKOH ANI TERHADAP DOMINASI PATRIARKI DALAM NASKAH BUNGA RUMAH MAKAN KARYA UTUY TATANG SONTANI: KAJIAN FEMINISME TENTANG OTONOMI PEREMPUAN DAN PEMBEBASAN DIRI.” - Ahlan Romadhona; Muhammad Afif Ardiansyah; Kartika Auliyah; Wawan Hermawan (Jurnal Padamu Negeri, 2026)
This study is motivated by the persistence of patriarchal structures in society that limit women’s roles, life choices, and autonomy, which are also represented in literary works. One work that reflects this condition is the drama script Bunga Rumah Makan by Utuy Tatang Sontani. This study aims to describe the forms of patriarchal domination experienced by the character Ani and to reveal the forms of resistance and self-liberation she undertakes. The research employs a qualitative descriptive method with a textual analysis approach. The research data consist of dialogues and stage directions in the drama script that illustrate power relations between male and female characters. The data are analyzed through the stages of data reduction, data presentation, and conclusion drawing using a feminist perspective. The findings show that the character Ani experiences various forms of patriarchal domination, including subordination, gender stereotyping, objectification, restriction of mobility, and verbal violence. This study concludes that Bunga Rumah Makan represents women as agents of self-liberation who struggle to break free from patriarchal structures, thereby positioning literary works as a medium of social and gender critique.